Moving to Java 9 : better design and simpler code (LiveLessons (Indianapolis, Ind.), 2017)
"Java 9 introduces new features and functions that will make your code simpler and easier to read and will make for better deployment and documentation as well. There are also a number of changes, however, that might have unexpected consequences for your applications. This video covers the advantages of Java 9 and how to manage risks when migrating an application to this version."--Resource description page